Strategy for the Global Musa Genomic Consortium: Report of the meeting held in Arlington, USA 17-20 July 2001 - International Network for the Improvement of Banana and Plantain (2002)
The Global Musa Genomics Consortium was launched at a meeting held in Arlington, Virginia, USA from 17-20 July, 2001. This meeting was attended by scientists from 12 countries worldwide. The meeting was critical for laying a solid foundation for future collaboration in Musa genomics and allowed the first important steps to be taken towards the development of a coherent strategy for Musa genomics. This included initiating the definition of tasks and their distribution among members of the Consortium.